2019
DOI: 10.1177/0363546519894301
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Comparison of Capsular Management Techniques During Hip Arthroscopy

Abstract: Background: Capsular management during hip arthroscopy remains controversial. Studies evaluating this topic consist mostly of retrospective comparative reviews of prospectively gathered data on a large series of patients. Purpose/Hypothesis: The purpose was to perform a prospective randomized trial to comparatively assess 3 commonly performed capsular management techniques. It was hypothesized that capsular closure during hip arthroscopy would result in superior outcomes when compared with unclosed capsulotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 30 publications
3
70
0
Order By: Relevance
“…Filan and Carton 11 found that 89.3% of patients who underwent capsular repair achieved the MCID for the mHHS, while 87.1% who had an unrepaired capsulotomy achieved the MCID for the mHHS, although this difference failed to reach statistical significance. Other comparative studies 10 have observed the trend toward increased yet nonsignificant rates of MCID achievement on the mHHS for patients with versus without capsular closure, while studies that have compared capsular management have reported significantly improved mHHS at latest follow-up when assessing raw scores but not MCID achievement. 8 , 31 Indeed, a recent meta-analysis of 10 studies with an evidence level of 4 or greater reported an improvement in the mHHS with capsular repair compared with nonrepair (mean difference, 4.01; P = .03), though it did not assess the MCID.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Filan and Carton 11 found that 89.3% of patients who underwent capsular repair achieved the MCID for the mHHS, while 87.1% who had an unrepaired capsulotomy achieved the MCID for the mHHS, although this difference failed to reach statistical significance. Other comparative studies 10 have observed the trend toward increased yet nonsignificant rates of MCID achievement on the mHHS for patients with versus without capsular closure, while studies that have compared capsular management have reported significantly improved mHHS at latest follow-up when assessing raw scores but not MCID achievement. 8 , 31 Indeed, a recent meta-analysis of 10 studies with an evidence level of 4 or greater reported an improvement in the mHHS with capsular repair compared with nonrepair (mean difference, 4.01; P = .03), though it did not assess the MCID.…”
Section: Discussionmentioning
confidence: 94%
“…Five studies 5 , 9 11 , 15 reported MCID achievement rates for the mHHS. For patients who underwent capsular closure, MCID achievement rates were in the range of 71% to 100%.…”
Section: Resultsmentioning
confidence: 99%
“…26 Regardless of the approach, capsulotomy closure has been shown to be beneficial following access to either compartment. 21,27,28 The management of labral tears in FAI is also debated.…”
Section: Discussionmentioning
confidence: 99%
“…In this Technical Note, we have described our preferred method for arthroscopic treatment of FAI, detailing a straightforward checklist of technical pearls that may be used to minimize complications and optimize patient outcomes. [17][18][19] Under-resection of cam lesions may lead to the need for revision hip arthroscopy 11,20 Failure to completely close the capsule may result in microinstability and worse clinical outcomes 21 DALA, distal anterolateral accessory; mMAP, modified mid-anterior portal.…”
Section: Discussionmentioning
confidence: 99%
“…This can eventually lead to iatrogenic hip instability and poor outcomes when excess capsular tissue is lost or unrepaired. Economopoulos et al, 3 in their prospective randomized study on capsulotomy versus capsular repair, showed that patients who underwent repair of the capsule achieved better surgical outcomes than those who had unrepaired interportal capsulotomies and T-capsulotomies. This finding further highlights the importance of careful and meticulous management of the capsular tissue.…”
Section: See Related Article On Page 1337mentioning
confidence: 99%